Philosophical and cultural aspects of the study "myth of Chernivtsi" - Dmytro Zhmundulak (Cхід, 2013)
The article examined the material cultural heritage of the city ofChernivtsi, the category "myth of the city" in the cultural aspects, the factors of urban culture, local and global aspects of multiculturalism.